Eastern European migrants' experiences of racism in English schools: positions of marginal whiteness and linguistic otherness. Issue 1 (2nd January 2019) - Tereshchenko, Antonina; Bradbury, Alice; Archer, Louise
ABSTRACT: The number of students in England registered as speaking the languages of Eastern, and Central Europe has grown significantly in the past decade, but these migrants' educational experiences remain under-researched. This study, based on interviews with students, parents and teachers in four secondary schools in London and in the East of England, found that Eastern European students experience various forms of racism and low expectations from teachers. Using a framework influenced by Critical Race Theory and critical conceptions of whiteness, we argue that these students occupy a position of marginal whiteness, related to their linguistic Otherness. However, as the parents we interviewed were aware, the students do benefit from whiteness if they speak English without an accent so that they are not perceived as 'foreign'.